Translating Meaning and Intention: Error Analysis of Indonesian Children Fairy Tale Subtitles on YouTube - Wisudawanto, Rahmat; Zaini, Khazaila (English Department, Universitas Negeri Surabaya, 2025)
This study investigates translation errors in the English subtitles of the Indonesian fairy tale Pohon yang Sombong (trans. The Arrogant Tree), with the aim of examining how meaning is transferred under the constraints of audiovisual translation. Subtitling is a complex process that requires not only accuracy in meaning but also adaptation to time, space, and readability limits, which become even more demanding when the audience is children. To address these challenges, the study employed a descriptive qualitative approach and applied the ATA Framework (2021), which classifies errors into three domains: target-language mechanics, transfer of meaning, and writing. The data consisted of all subtitle utterances from the chosen video, which were analyzed through content analysis and systematically categorized. The findings indicate that transfer-of-meaning errors were the most dominant, accounting for the majority of cases, particularly in the form of faithfulness errors. These errors reveal difficulties in preserving semantic and pragmatic equivalence, resulting in distortions of meaning that risk obscuring the intended message. Other types of errors included usage, syntax, omission, addition, and grammar, though these appeared less frequently. The results highlight the challenges faced by translators in maintaining accuracy while operating within subtitling constraints. The study concludes that improving subtitle quality requires greater emphasis on pragmatic awareness, cultural sensitivity, and child-oriented readability, alongside linguistic accuracy. Pedagogically, the findings underscore the importance of translator training and the value of applying systematic error analysis frameworks to ensure the clarity and educational function of subtitled children’s literature.